Dopamine, norepinephrine, and vasopressin accelerate particle transport velocity in murine tracheal epithelium via substance-specific receptor pathways: dependency on intra- and extracellular Ca2+ sources - Schmidt, Götz; Greif, Isabelle; Müller, Sabrina; Markmann, Melanie; Edinger, Fabian; Sander, Michael; Koch, Christian; Henrich, Michael (Frontiers in Pharmacology, 2024)
Background: The unique ability of the respiratory tract to protect the integrity of the airways by removing potentially harmful substances is defined as mucociliary clearance. This complex physiological mechanism protects the lower airways by ridding them of pollutants and pathogens. This study aimed to evaluate the potential influence of clinically relevant vasopressors on mucociliary clearance. Material and Methods: The particle transport velocity (PTV) of isolated murine tracheae was measured as a surrogate for mucociliary clearance under the influence of dopamine, norepinephrine, and vasopressin. Inhibitory substances were applied to elucidate relevant signal transduction cascades and the value and origin of calcium ions. Reverse-transcription polymerase chain reactions (RT-PCR) were performed to identify the expression of vasopressin receptor subtypes. Results: Dopamine, norepinephrine, and vasopressin significantly increased the PTV in a dosedependent manner with half maximal effective concentrations of 0.58 µM, 1.21 µM, and 0.10 µM, respectively. Each substance increased the PTV via separate receptor pathways. While dopamine acted on D1-like receptors to increase the PTV, norepinephrine acted on β-adrenergic receptors, and vasopressin acted on V1a receptors. RT-PCR revealed the expression of V1a in the murine whole trachea and tracheal epithelium. PTV increased when protein kinase A was inhibited and norepinephrine or vasopressin were applied, but not when dopamine was applied. Phospholipase C inhibition decreased the PTV when vasopressin was applied. In general, maximum PTV was significantly reduced when extracellular calcium entry was inhibited. When intracellular calcium stores were depleted, no increase in PTV was observed after administering all three substances. Inositol trisphosphate receptor activation was found to be pivotal in the increase in murine PTV after applying dopamine and vasopressin. Discussion: Dopamine, norepinephrine, and vasopressin accelerate the murine PTV via substancespecific receptor pathways. Further investigations should assess the value and interaction of these substances on mucociliary clearance in clinical practice.